Capture and Release Erythrocyte from the Blood with Thermoresponsive and Core‐Sheath PCL/PNIPAAm Nanofibers. Issue 5 (28th December 2015) - Shi, Qiang; Hou, Jianwen; Xu, Xiaodong; Gao, Jian; Li, Chunming; Jin, Jing; Wong, Shing‐Chung; Yin, Jinghua
Abstract : A newly developed nanofiber platform for nonadherent cell capture and release is demonstrated. The nanofiber platform is fabricated by single‐spinneret electrospinning of bovine serum albumin (BSA)‐conjugated poly( N ‐isopropylacrylamide) (PNIPAAm) and polycaprolactone blends. The nanofibers possess core‐sheath structure with PNIPAAm as the sheath, which render the nanofibers switchable between hydrophilicity and hydrophobicity with the temperature change. As a result of BSA immobilization on the sheath part, the nanofibers resist platelet adhesion in the blood, facilitating the direct capture and isolation of red blood cells (RBCs) from the blood. Meanwhile, the captured RBCs are readily released from the nanofibers with the temperature stimuli. The capture and release efficiencies of up to 100% are achieved while maintaining cellular integrity and function. This work presents a promising platform to capture and release nonadherent cell effectively for subsequent molecular analysis and disease diagnosis. Abstract : A nanofiber platform for cell capture and release, based on thermoresponsive, core‐sheath polycaprolactone/bovine serum albumin‐conjugated poly( N ‐isopropylacrylamide) nanofibers, is fabricated by single‐spinneret electrospinning. The platform, with the capability to resist platelets, can capture red blood cells from the blood directly and readily release the captured cells without damage.